2021
DOI: 10.1016/j.tranon.2021.101125
|View full text |Cite
|
Sign up to set email alerts
|

P-selectin glycoprotein ligand 1 promotes T cell lymphoma development and dissemination

Abstract: Highlights PSGL-1 protein is frequently expressed at the surface of malignant T cells. Enforced expression of PSGL-1 promotes T cell tumorigenesis in mice. PSGL-1 expression accelerates malignant T cell dissemination from tumors to several organs. PSGL-1 expression promotes malignant T cell expansion in kidneys and lungs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…20 Earlier research revealed that PSGL-1 promoted tumor growth and dissemination in mouse models of lymphoma and multiple myeloma. 36,39,40 The finding that PSGL-1 antibodies trigger malignant lymphoid cell death indicates that the selective advantage of PSGL-1 expression for lymphoma or leukemia development may render malignant cells vulnerable for targeted immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…20 Earlier research revealed that PSGL-1 promoted tumor growth and dissemination in mouse models of lymphoma and multiple myeloma. 36,39,40 The finding that PSGL-1 antibodies trigger malignant lymphoid cell death indicates that the selective advantage of PSGL-1 expression for lymphoma or leukemia development may render malignant cells vulnerable for targeted immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…20 Finally, in lymphoma mouse models PSGL-1 expression was found to promote lymphoma development and dissemination to distant organs. 39,40 Taking into consideration these findings, we sought to assess whether PSGL-1 could be a therapeutic target in lymphoma. Here, we report PSGL-1 expression at the surface of several human lymphoma cell lines.…”
Section: Introductionmentioning
confidence: 99%
“… 11 13 Cell surface glycoproteins such as CD44 and PSGL-1 interact with receptors expressed on endothelial cells, E- and P-selectins, and integrins. 7 , 14 21 This selectin–ligand interaction promotes the transient formation of membrane tethers and slings by HSPCs, resulting in their rolling along the endothelium at a shear stress of several dynes cm –2 generated by the blood flow. 2 , 3 , 22 …”
Section: Introductionmentioning
confidence: 99%
“…Hematopoiesis is the process of blood cellular component formation. It occurs during embryonic development and continues throughout adulthood to produce and replenish the blood system. Hematopoietic stem-cell delivery to specific sites in the body is central to many physiological functions from immunity to cancer metastasis. , During the process of “homing”, HSPCs extravasate through the endothelial cells from peripheral blood to the bone marrow and start repopulating it by producing hematopoietic lineage cells including red blood cells, white blood cells, platelets, granulocytes, and erythrocytes. The process of homing is initiated by tethering and rolling of the cells in flow followed by firm adhesion and transmigration into the tissue. , This is achieved by the cell’s interactions with the surface of the endothelium under the presence of external shear forces. Cell surface glycoproteins such as CD44 and PSGL-1 interact with receptors expressed on endothelial cells, E- and P-selectins, and integrins. , This selectin–ligand interaction promotes the transient formation of membrane tethers and slings by HSPCs, resulting in their rolling along the endothelium at a shear stress of several dynes cm –2 generated by the blood flow. ,, …”
Section: Introductionmentioning
confidence: 99%